Environmental Care Character Education Management Based on Green Mosques: Research at SMAN 3 Kuningan and SMPN 7 Cirebon - Rosanti, Atik; Jahari, Jaja; Mulyana, Mulyana; Suhartini, Andewi (International Journal of Social Science, Education, Communication and Economics, 2025)
This research is motivated by the increasing awareness of environmental care through the green mosque approach. The Green Mosque Movement itself is a strategic program to support the government's program in the Net-Zero carbon emissions target by 2060 and the character of caring for the environment. The aim of this research is to determine the planning, organization, implementation, supervision, supporting and inhibiting factors as well as the results of green mosque-based environmental care character education at SMAN 3 Kuningan and SMPN 7 Cirebon. This research is qualitative research with a naturalistic approach. The results of this research show (1) Planning for environmentally caring character education based on green Mosques was carried out with the help of a policy of integrating environmental education in subjects including religious education, citizenship education, and all subjects in schools, (2) Organizing was carried out by delegating tasks according to the plans and main tasks of school managers and stakeholders as well as organizing the learning components of environmentally caring character education based on green Mosques, (3) Implementing environmentally caring character education based on green Mosques by building a School Mosque that is full of environmentally caring character education values that are relevant to environmental learning with fulfills the 6 criteria for the green building concept, (4) Supervision of green mosque-based environmental care character education that has been planned can be used as a benchmark for the performance of the organizational structure that is led in carrying out its duties, (4) Supporting factors include the role of teachers, parents and the government, while the main obstacle at the start of construction was funding and design of the mosque design with the green mosques concept which is still relatively new. (5) As a result, green mosques-based mosques succeeded in forming students' environmental awareness and behavior, with environmentally friendly designs, sustainable use of resources, and the use of mosques as places for learning outside the classroom, which effectively instilled environmental care values and inspired students to apply them at home.